STUDY ON THE IMPLEMENTATION OF THE BADMINTON GAME IN EXTRACURRICULAR ACTIVITIES AT GRADES V. AND VI. - PRODEA, Cosmin; JOLDEȘ, Nicolae; POP, Ioan-Nelu (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2018)
The paper studies the impact of the implementation of the Badminton game extracurricular activities at secondary school level, and certain aspects relating to the benefits that the game of Badminton brings to the instructive-educational process. Thus, in addition to providing good health, the game of Badminton practiced in an appropriate manner by students at young ages, forms their team and competition spirit, strong characters and feelings of belonging to a community or idea, builds healthy moral values and creates elites. The idea is that Badminton proves to be one of the best ways to achieve the objectives of physical education and sport with regard to the development of the motor qualities of speed and skill. Even more, a constant interest of the students towards the game can be noticed. As a result, the game of Badminton is an alternative to the established sports, with a significant impact on the young generation. REZUMAT. Studiu privind implementarea jocului de badminton în activităţile extracurriculare la nivelul claselor a V-a și a VI-a. Lucrarea urmărește impactul implementării jocului de badminton în activitățile extracurriculare la nivelul treptei gimnaziale, și anume aspecte cu privire la beneficiile pe care jocul de badminton le aduce procesului instructiv-educativ. Astfel, pe lângă asigurarea unei stări bune de sănătate, jocul de badminton folosit în mod corespunzător de elevi, la vârste fragede, le formează acestora spirit de echipă și competiție, caractere puternice și sentimente de apartenență la o comunitate sau idee, induce valori morale sănătoase și creează elite. Ideea este că badmintonul se dovedește a fi o modalitate optimă de atingere a obiectivelor educației fizice si sportului cu privire la dezvoltarea calităților motrice viteza și îndemânarea. De asemenea se poate observa interesul susținut al elevilor față de jocul de badminton. Ca urmare, jocul de badminton este o alternativă la sporturile consacrate, cu un impact major asupra tinerei generații. Cuvinte cheie: Gimnaziu, Badminton, Extracurricular, Calități Motrice, Alternativă.